Transfusion‐related adverse events are decreased in pregnant women with sickle cell disease by a change in policy from systematic transfusion to prophylactic oxygen therapy at home: A retrospective survey by the international sickle cell disease observatory. Issue 6 (17th April 2018) - Ribeil, Jean‐Antoine; Labopin, Myriam; Stanislas, Aurélie; Deloison, Benjamin; Lemercier, Delphine; Habibi, Anoosha; Albinni, Souha; Charlier, Caroline; Lortholary, Olivier; Lefrere, François; De Montalembert, Mariane; Blanche, Stéphane; et al.
Abstract: Sickle cell disease (SCD) in pregnancy can be associated with adverse maternal and perinatal outcomes. Furthermore, complications of SCD can be aggravated by pregnancy. Optimal prenatal care aims to decrease the occurrence of maternal and fetal complications. A retrospective, French, two‐center study compared two care strategies for pregnant women with SCD over two time periods. In the first study period (2005‐2010), the women were systematically offered prophylactic transfusions. In the second study period (2011‐2014), a targeted transfusion strategy was applied whenever possible, and home‐based prophylactic nocturnal oxygen therapy was offered to all the pregnant women. The two periods did not differ significantly in terms of the incidence of vaso‐occlusive events. Maternal mortality, perinatal mortality, and obstetric complication rates were also similar in the two periods, as was the incidence of post‐transfusion complications (6.1% in 2005‐2010 and 1.3% in 2011‐2014, P = .15), although no de novo alloimmunizations or delayed hemolysis transfusion reactions were observed in the second period. The results of this preliminary, retrospective study indicate that targeted transfusion plus home‐based prophylactic nocturnal oxygen therapy is safe and may decrease transfusion requirements and transfusion‐associated complications.